SISTEM PENDUKUNG KEPUTUSAN UJI LAYAK JALAN KENDARAAN ANGKUTAN UMUM DI BANDAR LAMPUNG - Linda, Deppi; Hasyim, Lutfi (Jurnal Informatika, 2012)
Public transportations are already familiar to everyone in each province of Indonesia. Beside of the economic aspect, that is cheaper, public transportation also ease the way people to reach their destination. Based on that fact, each vehicle of public transportation must be roadworthy. Road test of public transportation vehicle in Department of Transportation will determine if the vehicle of public transportation is roadworthy or not. Decision Support System Road Test Of Public Transportation using FMADM (Fuzzy Multiple Attribute Decision Making) with Simple Additive Weighting (SAW) method is create with the purpose to take the machine year, vehicle year, condition of the exhaust emission, and the physical condition of the vehicle to determine the value of roadworthy. The estimation of each aspect will be written in roadworthy testing form and will be totalized as the final value. If the final value is greater than 100, the vehicle is not roadworthy. Whereas, if the final value is 100, the vehicle is roadworthy. In this case, it will take long while to determine if the vehicle is roadworthy or not. Keywords: SAW (Simple Additive Weighting), Vehicle and Due Diligence Vehicle.